Pathogenesis of Primary Foot-and-Mouth Disease Virus Infection in the Nasopharynx of Vaccinated and Non-Vaccinated Cattle. - Carolina Stenfeldt (PLoS ONE, 2015)
A time-course pathogenesis study was performed to compare and contrast primary foot-and-mouth disease virus (FMDV) infection following simulated-natural (intra-nasopharyngeal) virus exposure of cattle that were non-vaccinated or vaccinated using a recombinant adenovirus-vectored FMDV vaccine. FMDV genome and infectious virus were detected during the initial phase of infection in both categories of animals with consistent predilection for the nasopharyngeal mucosa. A rapid progression of infection with viremia and widespread dissemination of virus occurred in non-vaccinated animals whilst vaccinated cattle were protected from viremia and clinical FMD. Analysis of micro-anatomic distribution of virus during early infection by lasercapture microdissection localized FMDV RNA to follicle-associated epithelium of the nasopharyngeal mucosa in both groups of animals, with concurrent detection of viral genome in nasopharyngeal MALT follicles in vaccinated cattle only. FMDV structural and non-structural proteins were detected in epithelial cells of the nasopharyngeal mucosa by immunomicroscopy 24 hours after inoculation in both non-vaccinated and vaccinated steers. Co-localization of CD11c+/MHC II+ cells with viral protein occurred early at primary infection sites in vaccinated steers while similar host-virus interactions were observed at later time points in non-vaccinated steers. Additionally, numerous CD8+/CD3- host cells, representing presumptive natural killer cells, were observed in association with foci of primary FMDV infection in the nasopharyngeal mucosa of vaccinated steers but were absent in non-vaccinated steers. Immunomicroscopic evidence of an activated antiviral response at primary infection sites of vaccinated cattle was corroborated by a relative induction of interferon -α, -β, -γ and -λ mRNA in micro-dissected samples of nasopharyngeal mucosa. Although vaccination protected cattle from viremia and clinical FMD, there was subclinical infection of epithelial cells of the nasopharyngeal mucosa that could enable shedding and long-term persistence of infectious virus. Additionally, these data indicate different mechanisms within the immediate host response to infection between non-vaccinated and vaccinated cattle.